OPTIMIZATION OF COMPOSITION AND APPLICATION SCHEME OF CARBONITRIDING COATING FOR INCREASING THE SURFACE PROPERTIES OF TOOL STEELS - V. N. Fedulov (Литьë и металлургия, 2018)
The positive effect of using a new coating composition is primarily achieved due to the increase of the applied coating layer thickness to 20 mm on the hardened working surfaces of the tooling and due to introduction of gypsum in its composition. These actions improve the machinability of the coating application and the core formation on the surface of the heated coating of the crust, prevent emission of the gas phase from the reaction zone during heating in the furnace at 520 °C for 4 to 8 hours, as well as the use of strontium fluoride and an increase in the ferrocyanic potassium content. The diffusion capacity of the saturation process increases due to these actions. The use of a new composition, the change in the thickness of the layer, and also the fixation of the temperature regime of heating will ensure an increase in the operation life of the hardened tool parts by 1.5–2 times.